Exploring food system resilience to the global polycrisis in six Asian countries - Favas, Caroline; Cresta, Chiara; Whelan, Elizabeth; Smith, Kristie; Manger, Mari S.; Chandrasenage, Damith; Singhkumarwong, Anusara; Kawasaki, Jintana; Moreno, Susana; Goudet, Sophie (Frontiers in Nutrition, 2024)
The world is currently in the midst of a global food crisis brought about and exacerbated by a series of mutually reinforcing shocks to food systems. This study examined the resilience of food systems in six Asian countries (Bangladesh, Kyrgyz Republic, Lao PDR, Pakistan, Philippines, and Sri Lanka) amid the global 'polycrisis' caused by COVID-19, geopolitical conflicts, and climate change. The study employed a conceptual model assessing resilience through indicators measuring exposure to shocks, resilience capacities, strategies and outcomes. Trends in food imports, food security and cost of diets were analysed. The study's analysis of resilience capacities and agricultural and food diversity showed differing growth rates. Regarding resilience outcomes, there were notable upward variations in 2022, particularly in national food price inflation patterns, rice price anomalies in Lao PDR, and an increasing percentage of populations unable to afford a healthy diet in Sri Lanka and the Kyrgyz Republic.Additionally, a tightening of regional variability in food insecurity was observed for the Kyrgyz Republic during the crisis period. These findings highlight the diverse set of challenges and resilience capacities present in each country, influenced by a complex interplay of economic, political, agricultural, and food affordability factors, all of which are crucial in determining the long-term resilience of their food systems. The recommendations for future research include focusing on resilience assessment in food systems, integrating climate change adaptation measures, and developing early intervention strategies.